Migration in globalized sport : Finnish ice hockey players in Russia - Tarasanski, Alexandros (2016)
During the last five years the number of Finnish ice hockey players migrating to Russia has significantly increased. Despite this fact scarce research has been done in this field. Moreover, comparing to the progress that has been achieved in other areas of sociology of sport, much more work needs to be done, in sports transnational migration both at a theoretical and empirical level. Therefore, the purpose of this study is to examine how the migration period in Russia is perceived by Finnish professional ice hockey players by exploring and interpreting their personal experiences. More specifically, it is asked in this study for which reasons Finnish ice-hockey players migrate to Russia. Moreover, dimensions related to the adaptation process and how it affects the performance of the athletes among with the perceived by the players’ differences between the Finnish and Russian ice hockey cultures are examined. A qualitative phenomenological research method is applied in this thesis. This particular method fits well for the purpose of the study, because it allows to develop a composite description and interpretation of the essence of the experience of the professional Finnish ice hockey players who have migrated to Russia. The data is collected by semi-structured interviews of athletes who have played in Kontinental Hockey League (KHL) for Russian clubs. Thematic content analysis was utilized to analyze the collected data. The results of this study reveal, that it’s important to focus on the experiences of the migrants themselves as well as on the complexity of the relationships in which they are involved inside and outside the play of field. Under this focus the personal and professional motives of Finnish ice hockey players for migration are examined and discussed. Moreover, issues of adapting into a new environment both on and off the ice hockey ring are addressed, considering the cultural differences between Russia and Finland. Finally, from the data derived it seems that although commingle of sport cultures has taken place, the notion that a global homogenization of ice hockey culture is occurring is not supported. Implications for future research are also discussed, such as interviewing a larger number of players, immediately before their departure from Finland and right away after their arrival. Thus, deeper insights regarding the fulfillment of their expectations would be reached. This way, additional valuable information can be derived and applied by Finnish hockey players who intent to migrate to Russia.